Delivery of supported self‐management in remote asthma reviews: A systematic rapid realist review - Emma Kinley; Imogen Skene; Elizabeth Steed; Hilary Pinnock; Kirstie McClatchey (Wiley, 2022)
Abstract Background The COVID‐19 pandemic forced health care systems globally to adapt quickly to remote modes of health care delivery, including for routine asthma reviews. A core component of asthma care is supporting self‐management, a guideline‐recommended intervention that reduces the risk of acute attacks, and improves asthma control and quality of life. Objective We aimed to explore context and mechanisms for the outcomes of clinical effectiveness, acceptability and safety of supported self‐management delivery within remote asthma consultations. Design The review followed standard methodology for rapid realist reviews. An External Reference Group (ERG) provided expert advice and guidance throughout the study. We systematically searched four electronic databases and, with ERG advice, selected 18 papers that explored self‐management delivery during routine asthma reviews. Setting, Participants and Intervention Health care professional delivery of supported self‐management for asthma patients during remote (specifically including telephone and video) consultations. Main Outcome Measures Data were extracted using Context‐Mechanism‐Outcome (C‐M‐O) configurations and synthesised into overarching themes using the PRISMS taxonomy of supported self‐management as a framework to structure the findings. Results The review findings identified how support for self‐management delivered remotely was acceptable (often more acceptable than in‐person consultations), and was a safe and effective alternative to face‐to‐face reviews. In addition, remote delivery of supported self‐management was associated with; increased patient convenience, improved access to and attendance at remote reviews, and offered continuity of care. Discussion Remote delivery of supported self‐management for asthma was generally found to be clinically effective, acceptable, and safe with the added advantage of increasing accessibility. Remote reviews could provide the core content of an asthma review, including remote completion of asthma action plans. Conclusion Our findings support the option of remote delivery of routine asthma care for those who have this preference, and offer healthcare professionals guidance on embedding supported self‐management into remote asthma reviews. Patient and Public Contribution Patient and public contribution was provided by a representative of the Asthma UK Centre for Applied Research (AUKCAR) patient and public involvement (PPI) group. The PPI representative reviewed the findings, and feedback and comments were considered. This lead to further interpretations of the data which were included in the final manuscript.